Who Gets Left Behind? A Mixed-Methods Study on Climate-Smart Agriculture Access for Farmers with Disabilities in Tharaka Nithi, Kenya - Onyango, Rohin; Nzengya, Daniel; Lihasi, Lilian (Daystar University, School of Communication, 2025)
Climate-Smart Agriculture (CSA) enhances smallholder farmers' resilience; however, its accessibility for farmers with disability is neglected. Although socioeconomic and institutional barriers affect CSA adoption, the relationship between CSA and disability remains underexplored in climate resilience research. Ensuring access to CSA training and services for farmers with disability presents a challenge that undermines climate adaptation strategies' inclusivity. Without efforts to address physical, informational, and institutional barriers, CSA risks reinforcing inequalities in agricultural development. This study uses mixed methods to investigate CSA adoption and extension services access among smallholder farmers in Mukothima Ward, Tharaka Nithi, Kenya, focusing on farmers with disability. Quantitative data from a survey of 418 farmers (23 withdisabilities) is complemented by qualitative interviews, capturing barriers influencing CSA engagement across groups. The study found that farmers with disabilities had lower education levels and CSA adoption compared to non-disabled counterparts, highlighting disparities inaccesstoclimate-resilientpractices. Whiletheyreportedhigher participation in NGO-led CSA programs, they faced greater exclusion from government extension services and showed heightened vulnerability to climate shocks. This study contributes to inclusive climate resilience discourse by foregrounding disability as a critical yet overlooked axis in CSA research and policy. Findings underscore the need for interventions that address structural barriers and promote equitable access to CSA resources, supporting resilient rural livelihoods. These findings call for reimagining CSA through a disability-inclusive lens, where accessibility and tailored support are embedded within extension systems. Future research should prioritize farmers with disability to promote equitable climate adaptation in agriculture.
Conference Paper
Keywords: Climate-smart agriculture; Disability inclusion; Equitable access; Extension services; Climate resilience